Tipologi pola pengasuhan ibu bekerja, kemandirian dan adversity quotient anak - Umi Nur Hanifah (AN-NISA, 2020)
This study aims to analyze the typology of caring for working mothers towards the independence and adversity quotient of children. The environment around many women has a dual role which certainly influences the style of parenting towards children which leads to the formation of delinquency, the level of achievement and behavior of children. The process experienced by children who have working mothers has many demands and responsibilities in facing challenges that encourage the formation of independence and adversity quotient. Independence and adversity quotient become the context of research because not all children are able to be left by both parents working without paying attention, serving and protecting them. Yhis study uses a qualitative approach, a method of collecting data by conducting in-depth interviews, observation and documentation. The results of this study indicate that mothers who work as factory workers apply permissive parenting and children already have independence but do not yet have adversity quotient, mothers working as private employees apply authoritative parenting and children do not yet have independence but already have adversity quotient, mothers work as employees the country implements authoritative parenting the child has independence and has an adversity quotient, while the mother works as a market trader adopts an authoritative parenting and the child does not yet have independence but already has an adversity quotient.Penelitian ini bertujuan untuk menganalisis tipologi pengasuhan ibu bekerja terhadap kemandirian dan adversity quotient anak. Dilingkungan sekitar banyak wanita memiliki peran ganda yang tentunya berpengaruh pada gaya pengasuhan terhadap anak yang mengarah pada terbentuknnya kenakalan, tingkat prestasi dan perilaku anak. Proses dialami anak yang mempunyai ibu bekerja memiliki banyak tuntutan maupun tanggung jawab dalam menghadapi tantangan sehingga mendorong dalam pembentukan kemandirian dan adversity quotient. Kemandirian dan adversity quotient menjadi konteks penelitian karena tidak semua anak sanggup ditinggal kedua orang tuanya bekerja tanpa memperhatikan, melayani serta melindungi mereka. Penelitian ini menggunakan pendekatan kualitatif, metode pengumpulan data dengan melakukan wawancara mendalam, observasi dan dokumentasi. hasil penelitian ini menunjukkan bahwa ibu yang bekerja sebagai buruh pabrik menerapkan pola asuh permisif dan anak sudah memiliki kemandirian tetapi belum memiliki adversity quotient, ibu bekerja sebagai pegawai swasta menerapkan pola asuh otoritatif dan anak belum memiliki kemandirian tetapi sudah memiliki adversity quotient, ibu bekerja sebagai pegawai negeri menerapkan pola asuh otoritatif anak memiliki kemandirian dan memiliki adversity quotient, sedangkan ibu bekerja sebagai pedagang pasar menerapkan pola asuh otoritatif dan anak belum memiliki kemandirian tetapi sudah memiliki adversity quotient.